Krüppel-like factor 14, a coronary artery disease associated transcription factor, inhibits endothelial inflammation via NF-κB signaling pathway. (November 2018) - Hu, Wenting; Lu, Haocheng; Zhang, Jifeng; Fan, Yanbo; Chang, Ziyi; Liang, Wenying; Wang, Huilun; Zhu, Tianqing; Garcia-Barrio, Minerva T.; Peng, Daoquan; Chen, Y. Eugene; Guo, Yanhong
Abstract: Background and aims: Human genetic studies indicated that variations near the transcription factor Krüppel-like factor 14 ( KLF14 ) gene locus are highly associated with coronary artery disease. Activation of endothelial cells (ECs) by pro-inflammatory molecules and pathways is a primary step in atherosclerosis development. We aimed to investigate the effects and mechanism of KLF14 on inflammatory responses in ECs. Methods: Adenovirus-mediated overexpression of human KLF14 and EC specific Klf14 knockout mice were applied to study the role of KLF14 in EC inflammation. Intravital microscopy was used to examine leukocyte-endothelial cell interactions in vivo . Results: The expression of Klf14 was markedly decreased in mouse aortic ECs in both acute and chronic inflammatory conditions. Overexpression of KLF14 inhibited inflammatory activation of human ECs stimulated by interleukin 1β and tumor necrosis factor α. Primary pulmonary ECs from Klf14 knockout mice showed increased expression of adhesion molecules under IL-1β stimuli. Mechanistically, KLF14 inhibited NF-κB signaling pathway by transcriptionally suppressing the expression of p65, resulting in significantly decreased leukocyte adhesion to activated ECs. Using intravital microscopy, an increased leukocyte-endothelial cell interaction was observed in endothelial specific Klf 14 knockout mice compared to wild type control mice. Additionally, perhexiline, a KLF14 activator, induces KLF14 expression in ECs and reduced leukocyte-endothelial cell interactions in vitro and in vivo . Conclusions: The data revealed that KLF14 inhibited the inflammatory response in ECs and the protective effects were mediated by transcriptional inhibition of NF-κB signaling pathway. Endothelial KLF14 could be a potential therapeutic target for cardiovascular diseases. Graphical abstract: Highlights: KLF14, identified by human genetic studies, is associated with cardiovascular diseases. Endothelial function is highly correlated with cardiovascular events. The expression of KLF14 is downregulated in endothelial cells in both acute and chronic inflammatory conditions. KLF14 inhibits EC inflammation by direct repression of p65 transcription.